2021
DOI: 10.1155/2021/5677978
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Continuous User Authentication on Mobile Devices via Interaction Patterns

Abstract: Behavior-based continuous authentication is an increasingly popular methodology that utilizes behavior modeling and sensing for authentication and account access authorization. As an appearing behavioral biometric, user interaction patterns with mobile devices focus on verifying their identity in terms of their features or operating styles while interacting with devices. However, unimodal continuous authentication schemes, which are on the basis of a single source of interaction information, can only deal with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Thus, it was used in the training and testing of the model. While all features performed with high accuracies, the fusion of hand motion and hand posture features was an average of 95% with a top accuracy of 99%, compared with the top accuracy of just hand motion which was around 84%, and the top accuracy of hand posture which was around 95% (Zhang et al, 2021). When comparing F1 scores it was confirmed that the fusion of the features achieved the best performance.…”
Section: Related Wo Rksmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, it was used in the training and testing of the model. While all features performed with high accuracies, the fusion of hand motion and hand posture features was an average of 95% with a top accuracy of 99%, compared with the top accuracy of just hand motion which was around 84%, and the top accuracy of hand posture which was around 95% (Zhang et al, 2021). When comparing F1 scores it was confirmed that the fusion of the features achieved the best performance.…”
Section: Related Wo Rksmentioning
confidence: 82%
“…Authors in (Zhang et al, 2021), examined the use of phone movement dynamics as the sole biometric used in an authentication schema. Using the way a user motioned with their hand and the posture in which they held their device, the authors created a schema that used both dynamic and static iteration respectively to make an authentication decision.…”
Section: Related Wo Rksmentioning
confidence: 99%
“…Cao et al [16], Y. Wang et al [17], X. Zeng et al [18], and Q. Zou et al [19] utilize Convolutional Neural Networks (CNNs) and Long Short-Term Memory (LSTM) algorithms for mobile gait recognition using smartphone sensors. These systems collect data using an accelerometer [16], or an accelerometer and a gyroscope [17][18][19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The scheme verified user identities constantly by collecting multidimensional behaviour characteristics through online procedure, and locks out users if any strange behaviours were noticed. Hand motion and hold posture were combined to capture static and dynamic interaction patterns with mobile devices for continuous authentication [42]. Fusion of features could achieve better accuracy and also reduce equal error rate.…”
Section: Literature Surveymentioning
confidence: 99%